Reluctant partners coming together? : interface between people, government and the NGOs - Rajasekhar, D. 1960-; Biradar, R. R. 1960-; American Studies Research Centre (Hyderabad, India); Institute for Social and Economic Change (Bangalore); Interface between Government Agencies and the Target Group of NGOs (Workshop) (1999: ASRC Centre, Hyderabad); Reluctant Parners Revisited: Interface between Government, NGOs and People (Workshop) (1999: Institute for Social and Economic Change, Bangalore) (New Delhi : Concept, 2004)
Contributed papers presented at the workshops "Interface between Government Agencies and the Target Group of NGOs" held at ASRC Centre, Hyderabad on 21-23 Jan, 1999 and "Reluctant Partners Revisited: Interface between the Government, NGOs and people" held at the Institute for Social and Economic Change, Bangalore on 26-27 Aug, 1999with reference to India
Includes index
Keywords: Economic development project -- India, South -- Congresses; Administrative agencies -- India, South -- Congresses; Non governmental organizations -- India, South -- Congresses; Social action -- India, South -- Congresses